Healthy and active pre-retirement and retirement ages: elderly inequality in Latvia - Krumins, Juris; Berzins, Atis; Dahs, Aleksandrs; Ponomarjova, Denize (University of Latvia, 2019)
Pre-retirement and senior population groups are more affected by activity limitations, unemployment and bad perceived health than population in active ages. Data for Latvia and other EU countries demonstrate a warning situation – socio-economic inequalities among elderly are not diminishing as fast as was expected. The aim of the paper is to analyse healthy and active life in pre-retirement and retirement ages to detect changes and inequalities complying with active ageing and public health. Analysis is based on Population Census and SILC data on national, regional and smaller territorial level. Regression models are used to study causal links and relations between the underlying social and economic circumstances and the selected measures of inequality. Ethnic and professional background is considered among explanatory factors. A framework for the better understanding of elderly inequalities includes not only traditional demographic and socio-economic factors, but also regional determinants.
Keywords: active ageing; healthy life years; elderly inequality; mortality; Research Subject Categories::SOCIAL SCIENCES::Business and economics